Molecular identification of the corticosterone-sensitive extraneuronal catecholamine transporter - Gründemann, Dirk; Wogatzky, Birgit; Rappold, Gudrun; Schömig, Edgar (Nature neuroscience, 1998)
Catecholaminergic signaling regulates various physiological functions, such as blood pressure1 and is implicated in drug dependence, affective disorders and male aggressive behavior2,3. The actions of released catecholamines are terminated by sodium-driven, high-affinity transporters in the plasma membrane of the releasing neurons4,5 and by a corticosterone-sensitive, low-affinity, high-capacity extraneuronal transport system6, originally named uptake2, found in sympathetically innervated tissues7 and in central nervous system glia8. Here we report the molecular identification and pharmacological characterization of the extraneuronal catecholamine transporter, which is unrelated to the family of sodium-driven neuronal monoamine transporters5.
Gesehen am 29.03.2021